Suppression of essential pro-inflammatory signaling pathways by natural agents for the therapy of Multiple Myeloma - Sikka, S.; Shanmugam, M.; Kannaiyan, R.; Surana, R.; Shin, E.; Kumar, Alan Prem; Sethi, G.; Ahn, K. (Springer Netherlands, 2014)
Multiple myeloma (MM) is a malignant plasma cell tumor often arising in the bone marrow and is the most common non-Hodgkin’s haematological malignancy contributing 13 % of all malignancy and 1 % of neoplasia. MM arises from a pre-malignant condition known as ‘monoclonal gammapathy of undermined significance’. The aberrant antibodies that are produced leads to dysregulated humoral immunity. Studies in the last few years have revealed that various pro-inflammatory signaling pathways including nuclear factor-kappaB (NF-κB), signal transducer and activator of transcription 3 (STAT3), activator protein 1 (AP-1), phosphatidylinositol-3-kinase (PI3K/AKT), receptor Met and its ligand hepatocyte growth factor, and Wnt-β catenin play a pivotal role in the initiation and progression of MM. These signaling pathways can be induced by different pro-inflammatory cytokines and chemokines in MM cells. Hence, it is imperative to clearly dissect the role of various pro-inflammatory signaling pathways for the better understanding of the disease process and also for developing effective therapeutic interventions. In this review, we comprehensively analyze the detailed role of various pro-inflammatory signaling pathways involved in myeloma-genesis and its progression. Also, we discuss in detail the potential contribution of distinct inhibitors of pro-inflammatory signaling pathways derived from the natural sources that can be utilized both for the prevention and the treatment of MM.